Comprehensive testing for, and diagnosis of, sexually transmissible infections among Australian gay and bisexual men: findings from repeated, cross-sectional behavioural surveillance, 2003–2012. (14th November 2013) - Holt, Martin; Hull, Peter; Lea, Toby; Guy, Rebecca; Bourne, Chris; Prestage, Garrett; Zablotska, Iryna; de Wit, John; Mao, Limin
Abstract : Objectives: To analyse changes in testing for sexually transmissible infections (STI) among gay and bisexual men in Melbourne, Sydney and Queensland, Australia, particularly comprehensive STI testing (at least four tests from different anatomical sites in the previous year), and the characteristics of men who had such testing. Method: Data were analysed from repeated, cross-sectional, community-based surveys conducted during 2003–2012. Trends in specific STI tests and comprehensive testing were assessed and the characteristics of participants who reported comprehensive STI testing were identified using multivariate logistic regression, stratified by HIV status. Results: Among HIV-negative and unknown status men (n=51 009), comprehensive STI and HIV testing increased substantially from 13% in 2003 to 34% in 2012. During the same period, comprehensive STI testing (excluding HIV testing) increased from 24% to 57% among HIV-positive men (n=5532). In both HIV status groups, comprehensive testing was more commonly reported by men who had unprotected anal intercourse with casual partners, and men with higher numbers of partners. Among HIV-negative/unknown status participants, comprehensive STI and HIV testing was also associated with education level, regional location and finding partners online. Among HIV-positive men, comprehensive STI testing was also associated with free time spent with gay men and illicit drug use. Comprehensive testing was related to a high annual rate of diagnosis with STIs (20% of HIV-negative/unknown status men and 38% of HIV-positive men). Conclusions: There has been a substantial improvement in the proportion of gay and bisexual men in Melbourne, Sydney and Queensland who report comprehensive testing. Comprehensive testing is most likely among men whose practices put them at increased risk of infection, and is associated with a high rate of STI diagnosis. However, opportunities for comprehensive testing are still being missed, suggesting a need for its ongoing promotion.